Influence of crystalline polymorphism on the phase change properties of sorbitol-Au nanocomposites. (June 2019) - Liu, Xiaosong; Marbut, Cody; Huitink, David; Feng, Gang; Fleischer, Amy S.
Abstract: Phase change materials (PCMs) are widely purported in energy storage applications for reducing heating and cooling loads near the transition between solid and liquid phases. Recently, PCMs have gained interest for applications in passive cooling of electronic devices, which can alleviate temperature spikes that reduce the reliable lifetime of the electronics. In this application, sugar alcohols are gaining attention for use in power electronic systems because of their relatively high latent heat and suitable melting temperatures. In this study, the impact of gold nanoparticles on the thermal properties of D-sorbitol (a common sugar alcohol) are reported. Particular attention is paid to the crystallization process and impact on the formation of different crystal phases, since the crystallization process of sugar alcohols can be complicated with concomitant polymorphic crystallization of competing phases within the solid mixture. Here, it was observed that the addition of the nanoparticle in amount up to 0.002 wt% is found to create a minor increase (less than 7%) in the thermal conductivity of the sorbitol, a small decrease in the specific heat, and a significant increase in the latent heat of the sorbitol, up to 2× some cases. This increase is found to be highly dependent on the preferential phase formation of the sorbitol as influenced by the presence of Au nanoparticles. Highlights: Sorbitol has different crystalline forms which are affected by nanoparticle addition and crystallization temperatures. Adding 0.002 wt% nanoparticles led to a 7% increase in thermal conductivity. Melt temperature increased 10 °C with addition of Au nanoparticles in addition to increased latent heat capacity. One must understand the polymorphic nature of sorbitol for proper use as a PCM.